KEWIRAUSAHAAN PETANI DALAM PENGELOLAAN BISNIS MIKRO DI PEDESAAN - Dumasari Dumasari (UII, 2014)
This article aims to examine some of the determinants of entrepreneurial farmers and functions in the management of rural micro businesses. Some determinant factors of entrepreneurial farmers can be internal and external. Determinant factors also have the effect of enabling and inhibiting. Entrepreneurship of farmers have some strategic functions in development that encourage micro businesses in rural areas. Keywords : entrepreneurship, farmers, micro businesses and rural